2011
DOI: 10.1021/jo102107k
|View full text |Cite
|
Sign up to set email alerts
|

Annulation of Benzamides with [60]Fullerene through Palladium(II)-Catalyzed C−H Bond Activation

Abstract: Palladium-catalyzed heteroannulation of N-substituted benzamides with [60]fullerene, which proceeds through direct sp(2) C-H bond activation to form 7-membered ring pallada-intermediate with C(60), led to formation of [60]fulleroisoquinolinones in moderate to good yields (8-64% based on recovered C(60)). A plausible reaction pathway is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 80 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…of pTsOH in 6.2 mL of ODCB/TFA (6:0.2) at ambient temperature, the desired monofunctionalized fullerene product 2a was isolated in good chemical yield (37%; 48% based on converted C 60 , entry 9). K 2 S 2 O 8 was also an effective oxidant for this functionalization when compared to other metal oxidizing agents (entry 10 vs. entries [4][5][6][7][8]. We noted that increasing reaction temperature or time did not improve reaction yields (entries [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…of pTsOH in 6.2 mL of ODCB/TFA (6:0.2) at ambient temperature, the desired monofunctionalized fullerene product 2a was isolated in good chemical yield (37%; 48% based on converted C 60 , entry 9). K 2 S 2 O 8 was also an effective oxidant for this functionalization when compared to other metal oxidizing agents (entry 10 vs. entries [4][5][6][7][8]. We noted that increasing reaction temperature or time did not improve reaction yields (entries [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 91%
“…The reaction conditions were optimized with N-tosyl-2-aminobiphenyl (1a) as a model substrate and the results are summarized in Table 1. Initially, we attempted the present reaction with our previously reported conditions [4] using CuA C H T U N G T R E N N U N G (OAc) 2 as an oxidant in o-dichlorobenzene (ODCB)/trifluoroacetic acid (TFA) solvent (6:1) at 120 8C; unfortunately, no desired product 2a was observed (Table 1, entry 1). Neither was 2a observed without TFA in control experiments (entries 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, top) 46. Chuang, Wang, and co‐workers reported the palladium‐catalyzed synthesis of fulleroisoquinolinones by the annulation of C 60 with N ‐alkyl benzamides through CH activation (Scheme , bottom) 47. Trifluoroacetic acid was used as a key co‐solvent for improving the reaction performance.…”
Section: Annulation Of Amides With Arenesmentioning
confidence: 99%
“…Previous studies have recognized that some transition metals, such as palladium,3a–3e rhodium,3f3j cobalt,3k3m manganese,3n3q iron,3r,3s and copper,3t–3v can mediate functionalization of the fullerene sphere. In this context, we have recently also reported annulations of benzamides with [60]fullerene through palladium(II)‐catalyzed C–H bond activation4 to afford fullero‐isoquinolinones. In 1998, Cheng et al first reported a nickel‐catalyzed [2+2+2] cycloaddition between C 60 and a tethered diyne mediated by stoichiometric amounts of nickel complexes;5 this study is to date the only example of [60]fullerene functionalization mediated by nickel complexes.…”
Section: Introductionmentioning
confidence: 99%